2016
DOI: 10.3892/or.2016.5111
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and fructose-1,6-bisphosphate reduce the HEPG2 cell proliferation via increase of free radicals and apoptosis

Abstract: Hepatocellular carcinoma is the most prevalent type of tumor among primary tumors affecting the liver. Rapamycin is currently used as a basis for chemotherapy in the treatment of cancers, including the liver. Because it shows several adverse effects, minimizing these effects without compromising efficacy is important. In this sense other drugs may be used concomitantly. One of these drugs is fructose-1,6-bisphosphate (FBP), which has shown therapeutic effect in various pathological situations, having antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Suggestive of autophagy induction, the formation of the autophagosomes induced by F1,6BP treatment in EC cells corroborates with previous studies in cancer cells treated with the same molecule (Da Silva et al, 2016). This is the first report of F1,6BP-mediated autophagy in Ishikawa cells as far as we know.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Suggestive of autophagy induction, the formation of the autophagosomes induced by F1,6BP treatment in EC cells corroborates with previous studies in cancer cells treated with the same molecule (Da Silva et al, 2016). This is the first report of F1,6BP-mediated autophagy in Ishikawa cells as far as we know.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed an increase of ROS levels generated by treatment with F1,6 BP in human EC cells (Ishikawa). Studies have also identified that cancer cells may become vulnerable to PCD in response to exogenous F1,6 BP administration due to the induction of increased ROS levels (Da Silva et al, 2016; Li, Wei, Shen, & Hu, 2014; Lu, Yu, & Zhu, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Others showed that FBP induced oxidative stress in hepatic carcinoma cells, which caused an inhibition in proliferation, and this effect was suppressed when these cells were treated with anti-oxidants, such as N-acetyl-l-cysteine or catalase [12]. In contrast, using the same cell line, HepG2, FBP-treatment led to cell senescence, an increase in catalase activity [10] and a decrease in thiobarbituric acid reactive substances, which is a lipid peroxidation product and an indirect measure of radical oxygen species (ROS) [57]. Regardless of this discrepancy, there is a strong body of evidence suggesting that FBP has anti-oxidant properties [13] and, in the present study, FBP was able to increase expression of an antioxidant enzyme, SOD1, in FLF.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia can result in the activation of genes associated with angiogenesis and cell survival [ 146 , 147 , 148 ]. Many chemotherapeutic drugs cause DNA damage through generating free radicals [ 149 , 150 , 151 ]. Without oxygen however, the cytotoxicity of several chemotherapeutic drugs whose activity depends on generating free radicals is reduced.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%